2015
DOI: 10.1097/fjc.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Attenuates Monocrotaline-induced Pulmonary Arterial Hypertension in Rats

Abstract: Abstract:Calorie restriction (CR) is one of the most effective nonpharmacological interventions protecting against cardiovascular disease, such as hypertension in the systemic circulation. However, whether CR could attenuate pulmonary arterial hypertension (PAH) is largely unknown. The PAH model was developed by subjecting the rats to a single subcutaneous injection of monocrotaline. CR lowered mean pulmonary arterial pressure (mPAP) and reduced vascular remodeling and right ventricular hypertrophy in PAH rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Given that we cannot correlate both proteins (AMPK and mTOR) with the actual degree of PAP at any stage, this would be a limitation. However, in that sense, the literature supports and describes that CR could decrease PAP and RVH (Ding et al, 2015). Thence, in the current study, it is clear that with CR, and the hypoxia regimen increased the AMPK activity and inhibited mTOR, which might explain the RVH that was found.…”
Section: Discussionsupporting
confidence: 63%
“…Given that we cannot correlate both proteins (AMPK and mTOR) with the actual degree of PAP at any stage, this would be a limitation. However, in that sense, the literature supports and describes that CR could decrease PAP and RVH (Ding et al, 2015). Thence, in the current study, it is clear that with CR, and the hypoxia regimen increased the AMPK activity and inhibited mTOR, which might explain the RVH that was found.…”
Section: Discussionsupporting
confidence: 63%
“…The AAR of rat hearts was homogenized in 0.9 % NaCl (1:10, wt/vol). The tissue homogenate was centrifuged at 12,000 g for 10 min at 4 °C, and the supernatant was collected to determine myocardial eNOS activity using a spectrophotometrical assay kit (Nanjing Jiancheng Bioengineering) as previously reported [ 21 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acetylated eNOS antibody was not commercially available up to now. The expression of eNOS acetylation was determined by co-immunoprecipitation assay as described in our previous study [ 24 ]. eNOS (1:1000 crosslinked to magnetic beads (Dynal, Invitrogen) for extraction) was immunoprecipitated from 40 μg of myocardial tissue lysate, and the primary antibody for acetyl-lysine (Cell signaling) was employed to detect the association of the acetyl-lysine with eNOS by using immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
“…An activator of SIRT1 normalised SIRT1 expression in aged mice and restored endothelium-dependent vasodilatation by enhancing cyclooxygenase (COX)-2 signalling and reducing inflammation and oxidative stress in the elderly animals [ 99 ]. Another animal study showed that CR-improved endothelial function was associated with restored eNOS phosphorylation and SIRT1 expression, but reduced eNOS acetylation [ 100 ]. In eNOS-deficient mice, CR failed to exert an antihypertensive effect, as evidenced by elevated BP and absence of SIRT1 activity [ 101 ].…”
Section: Potential Mechanismsmentioning
confidence: 99%